ANALISIS PENGARUH KARAKTERISTIK PEKERJAAN DAN KEPUASAN KERJA TERHADAP KINERJA DOSEN PERGURUAN TINGGI SWASTA DI PALEMBANG - Roy yan Effendi (JURNAL KOMPETITIF, 2013)
The role of teachers is crucial in the success of an education. As educators, lecturers are not only required to be able to transfer knowledge to students, moreover lecturers shouldÃ‚Â  be able to nurture and develop students' scientific attitude, professionalism, discipline and dedicated in having responsibility with Tri Dharma of University. This research analyzes the effect of job characteristics and job satisfaction on the performance of economic lecturer in Private University Palembang. The research was conducted along 8 monts from march until October 2010. From the results of the trends, factors, and regression analysis, obtained the following information;1. Ã‚Â  81% economics lecturers of Private University in Palembang said they have agreed to serve as teachers therefore performance shown by the lecturers is good.2. Ã‚Â  75% economics lecturers of Private University in PalembangÃ‚Â  agreed that they try to give their best performance while doing duties and teaching obligation in their own universities. 3. Finally it can be concluded that the factors of job satisfaction and job characteristics have influenced and have close links with the performance of economic lecturer either silmutaneously or partialy in Private University in Palembang.Ã‚Â Key Word : job characteristics and job satisfaction economics lecturersÃ‚Â